Antimicrobial Resistance of Uropathogenic Escherichia coli from Elderly Patients at a General Hospital, Argentina - Delpech, Gastón (2018)
Background:Urinary Tract Infection (UTI) is a common cause of morbidity and mortality in older adults.Objective:To investigate antimicrobial resistance of uropathogenic Escherichia coli from elderly patients in a General Hospital, Argentina.Method:During the period July 2011-July 2015, patients over 70 years old with urinary tract infections, without urinary catheters and with noantimicrobial therapy the previous week before sampling, were included. Phenotypic characterization was carried out. In vitroqualitative and quantitative antimicrobial resistances were investigated. Antimicrobials assayed: ampicillin, amoxicillin-clavulanate,cefazolin, cefuroxime, cefoxitin, cefotaxime, ceftazidime, cefepime, imipenem, ertapenem, gentamicin, nalidixic acid, ciprofloxacin,trimethoprim-sulfamethoxazole (TMS) and nitrofurantoin. Patients? medical records were produced, and risk factors were analyzedby multivariate analysis.Results:768 bacterial isolates were identified as E. coli. Resistances to ampicillin (80.5%), nalidixic acid (61.7%), ciprofloxacin (42.8%),TMS (37.6%), amoxicillin-clavulanate (28.6%), cefazolin (21.6%), cefuroxime (20.7%), gentamicin (13.8%), cefotaxime (9.7%),ceftazidime (9.7%), cefepime (8.4%), cefoxitin (3.1%) and nitrofurantoin (2.3%) were observed. Resistance to carbapenems was notexpressed. Production of extended spectrum β-lactamases was detected (7.6%) in community acquired (96%) and healthcareassociated (4%) isolates. The independent risk factors for urinary infections produced by multi-resistant E. coli were: diabetesmellitus, recurrent infections, hospitalization during the last year and exposure to β-lactams in the last 3 months. Conclusion:A high prevalence of resistance to β-lactams and to other antimicrobials was observed. Detection of antimicrobial multi-resistantisolates highlights the need of antimicrobial resistance surveillance in elderly patients with urinary tract infections.